2006
DOI: 10.1055/s-2005-865634
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status of Interval-Trained Athletes in Various Sports

Abstract: Muscular exercise results in an increased production of free radicals and other forms of reactive oxygen species (ROS). Further, developing evidence implicates cytotoxins as an underlying etiology of exercise-induced stimuli in muscle redox status, which could result in muscle fatigue and/or injury. Two major classes of endogenous protective mechanisms (enzymatic and nonenzymatic antioxidants) work together to reduce the harmful effects of oxidants in the cell. This study examined the effects of acute physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 14 publications
2
16
1
2
Order By: Relevance
“…These findings are supported by previous literature, in particular with regards to higher oxidative stress in men compared to women [47] and in obese compared to overweight and/or normal weight subjects [48,49]. With regards to the antioxidant capacity in exercise-trained compared to untrained subjects, mixed results are available; some supporting our finding of lower antioxidant capacity in trained individuals [50] and some refuting this [51,52]. Those findings in support of our data may be linked to the acute increase in ROS experienced by exercise-trained individuals, which may partially deplete endogenous antioxidants over time [50].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are supported by previous literature, in particular with regards to higher oxidative stress in men compared to women [47] and in obese compared to overweight and/or normal weight subjects [48,49]. With regards to the antioxidant capacity in exercise-trained compared to untrained subjects, mixed results are available; some supporting our finding of lower antioxidant capacity in trained individuals [50] and some refuting this [51,52]. Those findings in support of our data may be linked to the acute increase in ROS experienced by exercise-trained individuals, which may partially deplete endogenous antioxidants over time [50].…”
Section: Discussionsupporting
confidence: 90%
“…This result is in contrast to literature reports on the effect of exhaustive effort in trained and untrained subjects: depending on the type of activity, both increased and decreased antioxidant enzyme activities and increased levels of DNA damage have been observed after strenuous effort, but this response was always less pronounced in well-trained athletes than in nonfit subjects (9,29,38).…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies showed a lower oxidative response in athletes than in controls both at rest and soon after M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 exercise, as malondialdehyde (MDA), protein carbonyls and 8-hydroxydeoxyguanosine resulted lower in trained compared with untrained subjects, while superoxide-dismutase (SOD) activity was higher in athletes compared to sedentary individuals [13,14]. Conversely, levels of antioxidant enzymes, such as catalase and glutathione-peroxidase, were higher than in sedentary subjects although these changes resulted sport-specific and related to the physical status and training level of athletes [15].…”
Section: Effects Of Exercise On Oxidative Stress and Healthmentioning
confidence: 84%